A literatura no ensino fundamental: um estudo sobre a qualificação docente e as estratégias de formação de leitores do Programa Aprendizagem na Idade Certa (PAIC) do Estado do Ceará - Moreira, Maria Efigênia Alves (2023)
This work aims to investigate the literature in elementary education in the State of Ceará, focusing on teacher training and reader training strategies proposed by the Axis of Literature and reader training, of the Programa Aprendizagem na Idade Certa 'Literacy in the Right Age Program' - PAIC. In order to do so, a survey was carried out on the teaching of literature in the State and its conception, based on the curricular guidelines, which guide the matrices of school curricula. The discussion about the teaching of literature is not new, it is present in many instances and forums because of the relevance that it expresses and is not still exhausted, since it needs to be re-signified due to the social dynamics, which proposes or imposes new flows, requiring a rethink about the presence of literature in the contemporary world. The discussions about the importance of literature in the school environment is a question of curricular power, when trends that strive for the teaching of competences and skills inquire about the validity of literature in occupying time in the school curriculum. During this investigation, topics related to children's literature suc as conceptions, importance and teaching in Brazil and Ceará were discussed. The initial and the continuing training of teachers of Pedagogy and Portuguese Language/Literature who will act as reading mediators in basic education was also discussed. In order to a better understanding of the Literature Axis and Reader Training, a quick presentation of its actions was carried out, but the focus is on the teacher training and on the proposed methodologies that promotes the work of teachers in the classroom as reading mediators. Among the employed methodologies, the Culture Circle applied to literature stands out, which promotes an aesthetic, cultural and dialogic formation, with a focus on reception. Within the scope of this research, in addition to the bibliographic and documentary survey, interviews with teachers who participated in the training and with the core manager of the Axis, which in 2022 completed fifteen years of implementation, were also carried out. This research is qualitative, and it applies a descriptive and explanatory method of procedure, and the technique used was bibliographic research, with the help of theorists who discuss literature, teaching, teacher training and reading mediation, in addition to data collection and analysis of results. Some of the consulted authors and works were Todorov (2009), Jouve (2012), Candido (2017), Patte (2012), Compagnon (2012), Bettelheim (2012) Lois (2010) and Cavalcanti (2004), Zilberman and Lajolo (2017), Zilberman and Magalhães (2005), Zilberman and Cademartori (2009), Souza (2006), Turchi (2016), Becker (2001), Coelho (2000), Colomer (2003), Antunes (2015, 2016), Costa (2013), Cosson (2016), Miguez (2009), Dalvi (2013), Rouxel (2013), Freire (2001, 2003, 2004), among others. This research is the first that focuses 9 on literature teaching methodologies within the scope of the Literacy at the Right Age Program (PAIC) and shows the importance of systematization and monitoring of reader training policies. In addition, it sets out to address reflections that can lead to other researches in the field of Reading in the school space, besides to pointing out ways to continue reader training policy in Ceará.